Utilizing Plastic Waste with Ecobricks: Creative Solutions for A Healthy and Waste-Free Life - Nasabella, Nazwa; Yushardi; Sudarti (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Indonesia ranks second as the largest producer of plastic waste in the world. Plastic waste takes about 1000 years to decompose. Cleaning up plastic waste is very difficult, because plastic waste has non-porous polymer properties, plastic can also cause temperatures to increase day by day. Plastic waste has a negative impact on the environment, such as environmental pollution due to the accumulation of waste. Anticipatory and preventive actions are needed to overcome this problem. The purpose of this research is to increase public awareness of the ecobrick method to utilize waste as an environmentally friendly material that has economic value. The research method used is a systematic literature review method, or called Systematic Literature Review (SLR) with results using an online article database